Genomic evolution of bovine viral diarrhea virus based on complete genome and individual gene analyses - Spetter, Lucas Maximiliano; Louge Uriarte, Enrique Leopoldo; Verna, Andrea Elizabeth; Odeon, Anselmo Carlos; González Altamiranda, Erika (Springer, 2024)
Bovine viral diarrhea virus (BVDV) genome consists of a single-stranded, positive-sense RNA with high genetic diversity. In the last years, significant progress has been achieved in BVDV knowledge evolution through phylodynamic analysis based on the partial 5′UTR sequences, whereas a few studies have used other genes or the complete coding sequence (CDS). However, no research has evaluated and compared BVDV evolutionary history based on the complete genome (CG), CDS, and individual genes. In this study, phylodynamic analyses were carried out with BVDV-1 (Pestivirus A) and BVDV-2 (Pestivirus B) CG sequences available on the GenBank database and each genomic region: CDS, UTRs, and individual genes. In comparison to the CG, the estimations for both BVDV species varied according to the dataset used, pointing out the importance of considering the analyzed genomic region when concluding. This study may provide new insight into BVDV evolution history while highlighting the need to increase the available BVDV CG sequences to perform more comprehensive phylodynamic studies in the future.